An examination of the predictive validity of the Structured Assessment of Risk and Need-Treatment Needs Analysis (SARN-TNA) in England and Wales - Tully, Ruth (Criminal justice and behavior, 2015)
The Structured Assessment of Risk and Need-Treatment Needs Analysis (SARN-TNA) is routinely used by the National Offender Management Service (NOMS) in England and Wales to aid assessment of risk of sexual offenders. This structured professional judgment tool?s predictive validity was examined with convicted sexual offenders in this field study. Receiver Operating Characteristic (ROC) was not significant at 2 years (Area Under the Curve [AUC] = 0.59, n = 304, p = .193) or at 4 years (AUC = 0.57, n = 161, p = .242). Survival analysis did not reveal significantly different sexual reconviction rates between SARN-TNA risk groups. Individual domains were also examined, with the sexual interests domain being the only predictive element of the SARN-TNA risk assessment tool. Results support further examination of how SARN-TNA risk group is calculated and more heavily weighting the importance of the sexual interests domain. The SARN-TNA should not be relied upon as a predictor scale of sexual reoffending.